NMR Signal Amplification by Reversible Exchange of Sulfur‐Heterocyclic Compounds Found In Petroleum. Issue 10 (15th July 2016) - Shchepin, Roman V.; Barskiy, Danila A.; Coffey, Aaron M.; Goodson, Boyd M.; Chekmenev, Eduard Y.
Abstract: NMR hyperpolarization via Signal Amplification by Reversible Exchange (SABRE) was employed to investigate the feasibility of enhancing the NMR detection sensitivity of sulfur‐heterocycles (specifically 2‐methylthiophene and dibenzothiophenes), a family of compounds typically found in petroleum and refined petroleum products. SABRE hyperpolarization of sulfur‐heterocycles (conducted in seconds) offers potential advantages of providing structural information about sulfur‐containing contaminants in petroleum, thereby informing petroleum purification and refining to minimize sulfur content in refined products such as gasoline. Moreover, NMR spectroscopy sensitivity gains endowed by hyperpolarization potentially allows for performing structural assays using inexpensive, low‐magnetic‐field ( ca . 1 T) high‐resolution NMR spectrometers ideally suited for industrial applications in the field. Abstract : Signal Amplification by Reversible Exchange (SABRE) enhances the NMR detection sensitivity of sulfur‐heterocycles (2‐methylthiophene and dibenzothiophenes), typically found in petroleum and refined petroleum products. SABRE hyperpolarization of sulfur‐heterocycles (conducted in seconds) offers potential advantages of providing rich structural information about sulfur‐containing contaminants in petroleum to guide petroleum purification and refining.